Comparative Genome Analysis of ‘Candidatus Phytoplasma luffae’ Reveals the Influential Roles of Potential Mobile Units in Phytoplasma Evolution - Huang, Ching-Ting; Cho, Shu-Ting; Lin, Yu-Chen; Tan, Choon-Meng; Chiu, Yi-Ching; Yang, Jun-Yi; Kuo, Chih-Horng (Frontiers in Microbiology, 2022)
Phytoplasmas are insect-transmitted plant pathogens that cause substantial losses in agriculture. In addition to economic impact, phytoplasmas induce distinct disease symptoms in infected plants, thus attracting attention for research on molecular plant-microbe interactions and plant developmental processes. Due to the difficulty of establishing an axenic culture of these bacteria, culture-independent genome characterization is a crucial tool for phytoplasma research. However, phytoplasma genomes have strong nucleotide composition biases and are repetitive, which make it challenging to produce complete assemblies. In this study, we utilized Illumina and Oxford Nanopore sequencing technologies to obtain the complete genome sequence of ‘Candidatus Phytoplasma luffae’ strain NCHU2019 that is associated with witches’ broom disease of loofah (Luffa aegyptiaca) in Taiwan. The fully assembled circular chromosome is 769 kb in size and is the first representative genome sequence of group 16SrVIII phytoplasmas. Comparative analysis with other phytoplasmas revealed that NCHU2019 has a remarkably repetitive genome, possessing a pair of 75 kb repeats and at least 13 potential mobile units (PMUs) that account for ∼25% of its chromosome. This level of genome repetitiveness is exceptional for bacteria, particularly among obligate pathogens with reduced genomes. Our genus-level analysis of PMUs demonstrated that these phytoplasma-specific mobile genetic elements can be classified into three major types that differ in gene organization and phylogenetic distribution. Notably, PMU abundance explains nearly 80% of the variance in phytoplasma genome sizes, a finding that provides a quantitative estimate for the importance of PMUs in phytoplasma genome variability. Finally, our investigation found that in addition to horizontal gene transfer, PMUs also contribute to intra-genomic duplications of effector genes, which may provide redundancy for subfunctionalization or neofunctionalization. Taken together, this work improves the taxon sampling for phytoplasma genome research and provides novel information regarding the roles of mobile genetic elements in phytoplasma evolution.